Comprehensive Small RNA-Seq of Adeno-Associated Virus (AAV)-Infected Human Cells Detects Patterns of Novel, Non-Coding AAV RNAs in the Absence of Cellular miRNA Regulation. - Catrin Stutika; Mario Mietzsch; Andreas Gogol-Döring; Stefan Weger; Madlen Sohn; Wei Chen; Regine Heilbronn (PLoS ONE, 2016)
Most DNA viruses express small regulatory RNAs, which interfere with viral or cellular gene expression. For adeno-associated virus (AAV), a small ssDNA virus with a complex biphasic life cycle miRNAs or other small regulatory RNAs have not yet been described. This is the first comprehensive Illumina-based RNA-Seq analysis of small RNAs expressed by AAV alone or upon co-infection with helper adenovirus or HSV. Several hotspots of AAV-specific small RNAs were detected mostly close to or within the AAV-ITR and apparently transcribed from the newly identified anti-p5 promoter. An additional small RNA hotspot was located downstream of the p40 promoter, from where transcription of non-coding RNAs associated with the inhibition of adenovirus replication were recently described. Parallel detection of known Ad and HSV miRNAs indirectly validated the newly identified small AAV RNA species. The predominant small RNAs were analyzed on Northern blots and by human argonaute protein-mediated co-immunoprecipitation. None of the small AAV RNAs showed characteristics of bona fide miRNAs, but characteristics of alternative RNA processing indicative of differentially regulated AAV promoter-associated small RNAs. Furthermore, the AAV-induced regulation of cellular miRNA levels was analyzed at different time points post infection. In contrast to other virus groups AAV infection had virtually no effect on the expression of cellular miRNA, which underscores the long-established concept that wild-type AAV infection is apathogenic.